Development of telligent controller for counter flow wet scrubber system - Umar, Sambo Aliyu (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Air pollution such as particulate matter (PM) emitted from industries result in several thousands of deaths. In recognition of this global threat, a large number of abatement measures have been taken to minimize the emission of this pollutant. Wet scrubber system has been the most widely used control device for PM contaminants. Its operating variables (gas velocity, temperature profile, particle size, liquid droplet's size, terminal settling velocity of liquid droplets, particle density and liquid to gas ratio) fluctuates randomly, thus resulting in a non-linear dynamic behavior of the system. This non linearity generally limits the ability of the scrubber to control the emission of PM2.5 and PM10 effectively below a set point of 20µg/m3, which is the maximum allowable emission limit of PM contaminants by world health organization (WHO). Attempts have been made using intelligent controllers to handle the non-linearity characteristics of the scrubber system, as such improving the performance of the system. However, the real time implementation of the intelligent controllers became a challenging issue. In this study, two intelligent controllers (fuzzy logic controller and adaptive neuro fuzzy controller) are developed for the proposed system. Adaptive neuro fuzzy controller shows a better control performance with a settling time of 5.2 seconds, hence implemented in real time on existing prototype of wet scrubber system using digital signal processor (DSP) Matlab interface. DSPs are high speed microcontrollers with low noise immunity when comparison to other classes of microcontrollers. The combined advantages of intelligent controller and DSP microcontroller have greatly improved the performance of wet scrubber system in terms of quick response to deliver the required scrubbing liquid droplet size based on the PM concentration level read by a dust sensor. The dust sensor placed at the scrubber exit measured the concentration of PM contaminants. Once the concentration of the contaminants is above the set point (20µg/m3), the intelligent controller will receive a signal from the DSP microcontroller indicating PM concentration level. The intelligent controller will then give an optimum droplet size needed to scrub the PM and the value will be communicated to the DSP through serial communication. The DSP microcontroller send appropriate input to the variable speed pump in the form of voltage which will be converted to flow rate value by the pump to deliver the required droplet through the spray nozzle. The scrubbing liquid provides a blanketing effect to entrap particles contaminants within the wet scrubber system. Result of simulation and real time results obtained at the best selected sampling time of 1 second shows that within short settling time of 9.4 seconds, the controller is able to track the set point and maintain the performance despite system disturbances. This study is limited to triangular and trapezoidal membership functions (MFs) in the controller development.